Halogen and halogen-free flame retarded biologically-based polyamide with markedly suppressed smoke and toxic gases releases. (1st March 2020) - Cai, Tongmin; Wang, Junling; Zhang, Chuanhui; Cao, Min; Jiang, Sujun; Wang, Xin; Wang, Bibo; Hu, Weizhao; Hu, Yuan
Abstract: Polyamide materials are regarded as one promising plastic, deriving from its exceptional physical and chemical properties. Unfortunately, the intrinsic high fire hazard (considerable heat, smoke and toxic gases generation) of polyamide strongly hinders its versatile applications. Utilizing suitable strategy to reduce its fire hazard has been more crucial. Here, the biologically-based polyamide materials are synthesized. In this work, the replacement of terephthalic acid with isophthalic acid contributes to the reduction on the melting point of polymer, which is beneficial to the processing in industry. It is found that PA10T/10I shows lower mechanical property and worse flammability than PA10T. By using halogen and halogen-free flame retardants, the dramatically reduced values of peak heat release rate can be observed. It is found that less halogen-free flame retardant are loaded to achieve V-0 rating, substantiating its higher flame retarded efficiency. Also the markedly improved limited oxygen index values are observed. TGIR results confirms the suppressed releases of toxic CO and HCN gases. Besides, the inhibited smoke generation can be found. Overall, both halogen and halogen-free strategy are effective in reducing the fire hazard of polyamide and halogen-free method show higher efficiency. Graphical abstract: Image 1